Optimasi modifikasi cross linking pati ganyong menggunakan natrium asetat terhadap kekambaan bahan, kemampuan menyerap air dan minyak - Iffah Muflihati; Nur Khikmah (AGROINTEK, 2023)
Canna starch is obtained from the extraction of canna tubers. Generally, the utilization of natural canna starch is still limited, whereas canna starch has disadvantages including large granule size, high viscosity level, low swelling power level, high retrogradation rate, not resistance to high pH, and pressure. Modification of cross-linking can improve to be resistant to mechanical stress and acid. The purpose of this study was to determine the optimization of cross-linking modification with sodium acetate on the bulk density and the ability of starch to absorb oil and water. This research uses Response Surface Methodology with Central Composite Design (CCD) model. With a factor of sodium acetate concentration and mixing time. Analysis of the research carried out are bulk density, OBC, and WBC. Modification of canna starch by cross-linking affects the starch produced, the presence of cross-linking in starch can strengthen the starch granules so that the starch granules are not easily gelatinized. The optimum condition bulk density was obtained from sodium acetate concentration of 25.1282% and mixing time of 34.1421 minutes with a bulk density of 0.626 g/cm3. In contrast to the optimum conditions for OBC obtained from sodium acetate 13.64% with a long mixing time of 33.57 minutes, the optimum conditions for measuring water absorption are 5.90%. Meanwhile, the optimum condition of WBC was obtained at a concentration of 13.64% sodium acetate with a mixing time of 33.57 minutes resulting in an optimum condition for measuring water absorption of 5.90%.